Usefulness of combined fractional anisotropy and apparent diffusion coefficient values for detection of involvement in multiple system atrophy - Ito, Mizuki (BMJ Group, 2007)
OBJECTIVE: To determine whether apparent diffusion coefficient (ADC) values and fractional anisotropy (FA) values can detect early pathological involvement in multiple system atrophy (MSA), and be used to differentiate MSA‐P (multiple system atrophy if parkinsonian features predominate) from Parkinson's disease (PD). METHODS: We compared ADC and FA values in the pons, cerebellum and putamen of 61 subjects (20 probable MSA patients, 21 age matched PD patients and 20 age matched healthy controls) using a 3.0 T magnetic resonance system. RESULTS: ADC values in the pons, cerebellum and putamen were significantly higher, and FA values lower in MSA than in PD or controls. These differences were prominent in MSA lacking dorsolateral putaminal hyperintensity (DPH) or hot cross bun (HCB) sign. In differentiating MSA‐P from PD using FA and ADC values, we obtained equal sensitivity (70%) and higher specificity (100%) in the pons than in the putamen and cerebellum. In addition, all patients that had both significant low FA and high ADC values in each of these three areas were MSA‐P cases, and those that had both normal FA and ADC values in the pons were all PD cases. Our diagnostic algorithm based on these results accurately diagnosed 90% of patients with MSA‐P. CONCLUSION: FA and ADC values detected early pathological involvement prior to magnetic resonance signal changes in MSA. In particular, low FA values in the pons showed high specificity in discriminating MSA‐P from PD. In addition, combined analysis of both FA and ADC values in all three areas was more useful than only one.